The mating mind: How sexual choice shaped the evolution of human nature - Miller, Geoffrey (London William Heinemann, 2000)
At once a pioneering study of evolution and an accessible and lively reading experience, The Mating Mind marks the arrival of a prescient and provocative new science writer. Psychologist Geoffrey Miller offers the most convincingand radicalexplanation for how and why the human mind evolved. Consciousness, morality, creativity, language, and art: these are the traits that make us human. Scientists have traditionally explained these qualities as merely a side effect of surplus brain size, but Miller argues that they were sexual attractors, not side effects. He bases his argument on Darwins theory of sexual selection, which until now has played second fiddle to Darwins theory of natural selection, and draws on ideas and research from a wide range of fields, including psychology, economics, history, and pop culture. Witty, powerfully argued, and continually thought-provoking, The Mating Mind is a landmark in our understanding of our own species.